Pengaruh Organizational Green Culture Terhadap Hospital Performance Dengan Green Innovation Sebagai Variabel Moderasi Pada Rumah Sakit Di Jawa Tengah: Systematic Literatur Review - Putri, Shella Vina; Anindita, Rini; Iswanto, Heri (Jurnal Manajemen dan Administrasi Rumah Sakit Indonesia (MARSI), 2026)
Hospital performance is a crucial aspect that requires continuous evaluation to ensure the quality of healthcare services, operational efficiency, and compliance with applicable regulations. In recent years, hospital performance issues have been suspected to be influenced by increasingly stringent government regulations regarding the implementation of green innovation in the healthcare industry. Furthermore, suboptimal hospital performance is also suspected to be related to the low implementation of organizational green culture as a foundation for a work culture oriented towards environmental sustainability. This article aims to analyze the influence of Organizational Green Culture on Hospital Performance with Green Innovation as a moderating variable based on a review of scientific articles from the last five years. The method used is a Systematic Literature Review. The SLR method is carried out by examining relevant scientific articles indexed in national and international databases, using predetermined inclusion and exclusion criteria. The results of the literature review indicate that organizational green culture influences hospital performance and green innovation moderates the influence of organizational green culture on hospital performance. It can be concluded that based on the selected articles, green innovation can moderate the influence of organizational green culture on hospital performance.